Efektivitas Dakwah tentang Tauhid: Studi Kasus YouTube Adi Hidayat Official - Tokan, Allvares Lesu; Irfani, H.Fahmi; Pesha, Indry Nirma Yunizul (VISA: Journal of Vision and Ideas, 2024)
Dakwah about tauhid has an important role in understanding the beliefs and understanding of the religion of the Muslim. In today's digital age, online platforms like YouTube have become a significant means of spreading the message to a large audience. The study aims to measure the effectiveness of the outreach of Tauhid through the YouTube channel Adi Hidayat Official. The research method used is a case study with a qualitative approach. The data was collected through observations of the content of the news feeds delivered through the YouTube channel as well as interviews with viewers to understand the impact of such news on their understanding of tauhid. The results of this research are expected to provide an insight into the extent to which YouTube news can be effective in disseminating the understanding of Tauhid to the wider public.